Lewis Arundel, or The railroad of life, no. 10 - http://id.worldcat.org/fast/2013271 (London : Virtue, Hall & Virtue, 1852., 1852)
Chapter one the train starts and the reader is introduced to three first class passengers. It proceeds to the Life and Times of Lewis Arundel.